SEMANTIC RELATIONS IN COMPLEX SENTENCES EXPRESSION AND INTERPRETATION OF MEANING (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract: The exploration of semantic relations in complex sentences stands as a cornerstone for understanding how human languages convey intricate layers of meaning. Within the spectrum of linguistic devices, complex sentences serve not only as structural tools but also as powerful media for packaging and interpreting nuanced bonds between separate ideas, events, participants, and actions. While surface-level syntax orchestrates the arrangement of clauses and markers, it is the semantic undercurrents—relations such as cause, condition, purpose, concession, time, place, and comparison—that imbue complex sentences with logical cohesion and expressive depth.